Faktor-faktor yang mempengaruhi status Gizi balita Di Posyandu Tamantirto Kasihan Bantul. - Sabniyanto (PSIK 13 UMY 315, 2013)
This study aims to determine the factors that affect the nutritional status of children in Posyandu Carnations A hamlet Gatak Tamantirto Kasihan Bantul Yogyakarta in 2013. This study uses cross-sectional method. The sample in this study was a toddler at the Posyandu Carnations A village Gatak, Tamantirto Kasian Bantul Yogyakarta. The data used are primary and secondary data. The results showed that (1) there is a significant relationship between maternal employment with the nutritional status of children in Posyandu Carnations A Village Gatak, Tamantirto, Kasian Bantul, (2) there is a significant relationship between mother's education level with the nutritional status of children in Posyandu Carnation A Village Gatak, Tamantirto, Kasian Bantul, (3) there is no significant relationship between family income per month with the nutritional status of children in Posyandu Carnations a Village Gatak, Tamantirto, Kasian Bantul and (4) there is a significant relationship between knowledge of the nutritional status of mothers with toddlers A Village in Carnation Posyandu Gatak, Tamantirto, Kasian Bantul.